2020
DOI: 10.48550/arxiv.2009.08184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A pair correlation problem, and counting lattice points with the zeta function

Abstract: The pair correlation is a localized statistic for sequences in the unit interval. Pseudo-random behavior with respect to this statistic is called Poissonian behavior. The metric theory of pair correlations of sequences of the form (anα) n≥1 has been pioneered by Rudnick, Sarnak and Zaharescu. Here α is a real parameter, and (an) n≥1 is an integer sequence, often of arithmetic origin. Recently, a general framework was developed which gives criteria for Poissonian pair correlation of such sequences for almost ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In 1998 Rudnick and Sarnak [RS98], showed that the 2-point correlation (or pair correlation) of (1.3) is Poissonian for any integer θ ≥ 2, and (Lebesgue) almost every α > 0. Two decades later [AEBM21] and [RT21] proved the same statement for all non-integer θ > 1, and 0 < θ < 1 respectively. However, excluding these metric results, very little is known about sequences on the unit interval growing with polynomial rate.…”
Section: Historymentioning
confidence: 68%
“…In 1998 Rudnick and Sarnak [RS98], showed that the 2-point correlation (or pair correlation) of (1.3) is Poissonian for any integer θ ≥ 2, and (Lebesgue) almost every α > 0. Two decades later [AEBM21] and [RT21] proved the same statement for all non-integer θ > 1, and 0 < θ < 1 respectively. However, excluding these metric results, very little is known about sequences on the unit interval growing with polynomial rate.…”
Section: Historymentioning
confidence: 68%
“…We follow the method from [12], [4], [1] to give the proof of Lemma 8 below. Generally speaking, our bound ( 19) is close to the optimal one, see [5].…”
Section: The Proof Of the Main Resultsmentioning
confidence: 99%
“…On the other hand, GRH implies [2] that n p = O(log 2 p) (the best unconditional bound belongs to Burgess [7] who proved n p ≪ p 1 4 √ e +o (1) ). Thus in the integer case our Theorem 1 gives upper bound (3) of a comparable quality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For θ ∈ N >1 , Rudnick and Sarnak [RS98] proved the metric Poissonian pair correlation of (1.3) in the late 90s. The case of non-integer θ > 1 was only recently settled by Aistleitner, El-Baz, and Munsch [AEBM21]. The regime θ < 1 will be addressed in a forthcoming work of Rudnick and the second named author, see [RT].…”
Section: Metric Poisson Pair Correlationmentioning
confidence: 99%